Aplicação do algoritmo bioinspirado Novel Bat Algorithm na parametrização dos controladores suplementares de amortecimento e dispositivo FACTS GUPFC - Miotto, Ednei Luiz (2018)
This work presents the Novel Bat Algorithm as a new technique for the to perform the coordinated tuning of the parameters of the supplementary damping controllers (Power Systems Stabilizers and Generalized Unified Power Flow Controller - Power Oscillation Damping) in multi-machine electric power systems. The main objective is to insert damping to low-frequency oscillations and thus ensure the stability of the electrical system against minor disturbances. The Power Sensitivity Model is used to represent the system. Thus, all devices and their components are modeled by power injection. Static and dynamic analyzes were performed in the two systems: the two-areas symmetric, and the New England. The performance of the proposed methodology (Novel Bat Algorithm), for tuning of the parameters of the controllers was compared to four other algorithms, presented in the literature: The Particle Swarm Optimization method, Bacterial Foraging Optimization method, Bat Algorithm method and a Genetic Algorithm with elitism. The results demonstrated that the Novel Bat Algorithm was more effective than the other techniques presented, generating robust solutions when variations on the scenarios of loads were considered, and therefore accredited it as a tool in the analysis of the study of small-signal stability.